Single Nucleotide Polymorphisms (SNPs) Genotypic Profiling Of Malay Patients With And Without Helicobacter Pylori Infection In Kelantan - Maran, Sathiya (2012)
Since first reported in 1986 in Malaysia by the Malaysian Pathology Society, differences in the Helicobacter pylori (H. pylori) prevalence among the three major ethnics has been much characterized. The state of Kelantan, situated at the north-eastern region of Peninsular Malaysia is unique with Malays comprising 90% of its population. There is an exceptionally low prevalence rate of H. pylori reported from this region, in the range of 4-5%. The exact reasons for the low prevalence rate of H. pylori infection are unknown.